Financial Inclusion and Socio-Demographic Determinants of Micro and Small Enterprise Performance: Evidence from Conventional, Islamic, and Non-User Segments in Jakarta, Indonesia - Irma Citarayani; Hermanto Siregar; Irfan Syauqi Beik; Alla Asmara (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Micro and Small Enterprises (MSMEs) as part of MSMEs have an important role in the national economy, including increasing economic growth, supporting economic stabilization, improving public welfare, alleviating poverty, and reducing unemployment rates. However, in its development, MSMEs face many challenges, including capital problems and low access to financial service institutions. Meanwhile, financial inclusion is one of the government's efforts to provide greater access to MSME actors so that they can use financial products and services. This study aims to determine whether financial inclusion and socio-demographic factors can affect MSME performance. The research methods used are multiple regression analysis, interaction test, and ANOVA tests. The study results indicate that financial inclusion significantly positively impacts Micro and Small business Performance in the DKI Jakarta area. This study also shows that socio-demographic factors, especially gender, business age, and generation of MSME actors, significantly influence MSME performance in the DKI Jakarta area. On the other hand, this study provides information that the perception of the performance of MSESs using conventional financial service institutions has a higher value than that of MSESs using sharia financial service institutions. Meanwhile, the lowest perception of MSES performance is held by MSES actors who do not use financial service institutions.